Analysis Of Human Relations And Physical Work Environment Conditions On Employee Work Ethic At Rskj Soeprapto Bengkulu Province 2025 - Rusli, Herpatika; Nurdan, Jon Hendri; Theresiana, Yunita (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Work ethic is a crucial factor in determining employee performance quality, especially in mental health service institutions. A poor work ethic can lead to decreased service quality and hinder institutional goals. This study aims to identify the factors influencing the work ethic of employees at Soeprapto Mental Hospital, Bengkulu Province, in 2025. A quantitative approach with a cross-sectional design was employed. A total of 92 permanent employees were selected using systematic random sampling. The independent variables included human relations, motivation, physical work environment conditions, work discipline, and job satisfaction. Data were collected using a structured questionnaire and analyzed through univariate, bivariate (Chi-square test), and multivariate analysis using binary logistic regression with the Backward LR method. The results revealed significant associations between all independent variables and employee work ethic (p < 0.05). However, multivariate analysis showed that only human relations and motivation had a statistically significant effect. Human relations emerged as the most dominant factor (Exp(B) = 14.241, p = 0.000), indicating that employees with good interpersonal relationships are 14 times more likely to demonstrate a strong work ethic. Motivation also showed a significant effect (Exp(B) = 4.266, p = 0.017). In conclusion, improving work ethic among hospital employees requires strategic efforts focused on fostering positive interpersonal relationships and enhancing both intrinsic and extrinsic motivation.